Inhibitors of Human Neuraminidase Enzymes Block Transmigration in vitro - Howlader, Md. Amran; Guo, Tianlin; Cairo, Christopher W. (Frontiers in Molecular Biosciences, 2022)
Cell migration to a site of inflammation is an important step of the immune response. This process is coordinated by cytokines, receptors, and the signal processing machinery of the cell. Many cellular receptors are glycosylated, and their activity can be modulated through changes in glycan structure. Furthermore, glycosylation can be critical to the folding and trafficking of receptors. In this work, we investigated the role of native human neuraminidase enzymes (NEU) in transmigration. We used a cultured T cell line (Jurkat) and a transwell assay with fibronectin (FN) coated wells and cytokines (IL-4 and TNF-α) as chemoattractants in the bottom chamber. We observed that NEU1, NEU3, and NEU4 were positive regulators of transmigration using an siRNA knockdown. Furthermore, we found that pharmacological inhibition of these enzymes inhibited transmigration. We conclude that human NEU isoenzymes NEU1, NEU3, and NEU4 can act as positive regulators of transmigration and should be investigated as targets for anti-inflammatory strategies.